Frequent activating HRAS mutations in trichilemmoma. (30th September 2014) - Tsai, J.‐H.; Huang, W.‐C.; Jhuang, J.‐Y.; Jeng, Y.‐M.; Cheng, M.‐L.; Chiu, H.‐Y.; Kuo, K.‐T.; Liau, J.‐Y.
Summary: Background: Trichilemmoma is a benign follicular epithelial tumour exhibiting outer root sheath differentiation. It is associated with Cowden syndrome and naevus sebaceus (NS), but the pathogenesis of sporadic tumours is poorly understood. Recently, NS was found to be caused by postzygotic HRAS or KRAS mutations. Objectives: We sought to determine whether NS‐related and NS‐unrelated trichilemmomas harbour RAS mutations. Methods: Formalin‐fixed and paraffin‐embedded blocks of 12 NS‐related and 15 NS‐unrelated trichilemmomas from 26 individuals were retrieved and analysed to determine the presence of mutations in exons 1 and 2 of the HRAS, KRAS and NRAS genes by polymerase chain reaction and direct sequencing. Mutational hotspots of the FGFR3 and PIK3CA genes were also analysed for NS‐unrelated cases. Results: Among the 27 cases, mutually exclusive HRAS c.37G>C and c.182A>G mutations were observed in 17 and three tumours, respectively. Of the 12 NS‐related tumours, 11 (92%) harboured the HRAS c.37G>C substitution. Of the 15 sporadic tumours, nine (60%) harboured HRAS mutations, including six c.37G>C and three c.182A>G. An HRAS c.182A>G mutation was observed only in sporadic tumours. No mutations were observed in the other genes that were tested. Conclusions: The high frequency of HRAS activating mutations, including the c.182A>G substitution, which was rather rare in NS, suggests that most trichilemmomas are authentic neoplasms. Abstract : What's already known about this topic? Virtually all cases of naevus sebaceus (NS) are caused by postzygotic HRAS or KRAS mutations. Trichilemmoma is among the most common secondary tumours associated with NS. What does this study add? Sporadic trichilemmomas frequently harbour activating HRAS mutations, including the c.182A>G substitution, which is rather rare in NS. The high frequency of activating HRAS mutations suggests that most trichilemmomas are authentic neoplasms.